Dextran sulfate microparticles encapsulating isoniazid and/or rifabutin as carriers for pulmonary tuberculosis therapy - Musacchio, Flavia (2019)
Tuberculosis (TB) is an active deadly pathology with high prevalence worldwide, occurring upon infection with Mycobacterium tuberculosis (MTB). Although conventional oral therapy is effective, it is associated with severe side-effects. The need to overcome these effects, which often lead to patient incompliance, demands alternative therapies, either by using new drugs or exploring new routes of administration of traditional drugs. The latter approach has been gaining popularity, as it could permit the reduction of used doses and the frequency of administration. Using the lung route would provide direct administration of antibiotics to the alveoli, where macrophages hosting the bacillus are located, which potentially comprises a successful approach. This study proposes the establishment of inhalable therapy, using dextran sulfate microparticles as carries of antitubercular drugs. This polysaccharide has structural residues/groups reported to be recognised in a preferential manner by alveolar macrophages, which increases the potential of the system in tuberculosis treatment. Microparticles were produced by spray-drying and characterized for morphology (SEM), Feret’s diameter, bulk and tap densities. The theoretical aerodynamic diameter (daer) was further calculated. The cytotoxic evaluation was performed in alveolar epithelial cells (A549) by the MTT assay. Microparticles were obtained with sizes varying within 1.1 and 1.9 μm, which potentiates phagocytosis. Theoretical daer between 1 and 1.4 μm suggests the adequacy of the carriers for the purpose of reaching the alveolar zone. The cytotoxic evaluation evidenced absence of toxicity. The generality of results provided encouraging indications to continue studying the potential of dextran sulfate microparticles as inhalable tuberculosis therapy.